Course note delivery on mobile facebook / Serge Gabarre, Cecile Gabarre and Rosseni Din - Gabarre, Serge (Penerbit UiTM (UiTM Press), 2016)
The present study reports on a longitudinal research which sought to explore how Facebook on smartphones could be used to replace an institutional learning management system. A review of the literature revealed that very little articles had been published on the incorporation of both technologies in education. A grounded action research method was employed over a period of one and a half year in three French as a foreign language courses. The action research implementation was two-fold as it included the delivery of course notes and the sharing of learner-created documents. Data collection was conducted through online observations and interviews. A systematic grounded theory approach was used during the six cycles of analysis. Findings revealed issues with the implementation which were corrected over time. Overall, students positively responded to the new platform of delivery. A working model describing learning a foreign language with Facebook on smartphones was constructed, and best practices guidelines were identified. These are discussed in the perspectives of mobile assisted language learning, task-based learning, and social networking learning.